Assessment of Environmental Impact of Contruction Projects: Asphalt - Hengki Junata; Ramdan Yusuf; Dewanto; Wiwid Suryono (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
The construction industry contributes significantly to environmental degradation. Environmental impact assessment (EIA) is becoming an important instrument to minimise the negative impacts of construction projects. Certification and compliance with green building standards are increasingly important to promote sustainable development. The objectives of this study are to evaluate the effectiveness of EIA in minimising the environmental impact of construction projects and to assess the readiness of the construction industry in adopting green building certification and compliance. This research is a type of literature review research related to EIA, green building regulations, and construction project case studies. The results concluded that EIA is effective in identifying and minimising the environmental impacts of construction projects. However, there are several obstacles in its implementation, such as the lack of experts and weak law enforcement. Green building certification and compliance are still not widely adopted by the construction industry in Indonesia. Furthermore, to strengthen the implementation of EIA and improve the readiness of the construction industry in adopting green building certification and compliance. This can be achieved through education, training, and incentives for developers and contractors.